Pengaruh Kepemimpinan, Kompetensi dan Organizational Citizenship Behavior terhadap Kinerja Karyawan dengan Motivasi sebagai Variabel Intervening pada Bank Sumut Syariah Cabang Brigjend Katamso - Siti Nurhamsiah; Muhammad Yafiz; Nur Ahmadi Bi Rahmani (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Human resources are an important factor for the company, because they serve as a driving force for the company's operations. Factors that can measure employee performance are leadership, competence, organizational citizenship behavior (OCB), and motivation. The purpose of this study was to find out how much influence leadership, competence, organizational citizenship behavior (OCB), and motivation have on employee performance at Bank Sumut Syariah Brigjend Katamso Branch. This study uses three independent variables, namely leadership, competence, and organizational citizenship behavior (OCB). Motivation as an intervening variable and employee performance as the dependent variable. The sampling method uses saturated sampling technique. The samples obtained were 30 respondents. The results showed that leadership had no significant effect on motivational variables, competency variables had a positive and significant effect on motivational variables, organizational citizenship behavior had a positive and significant effect on motivational variables, leadership variables had no significant effect on employee performance variables, competency variables had no effect positive and significant on employee performance variables, organizational citizenship behavior variable has no positive and significant effect on employee performance variables, motivational variables have no positive and significant effect on employee performance variables, leadership variable through motivational variables indirectly does not have a positive effect on employee performance variables, competency variable through motivational variable indirectly has no positive effect on employee performance variable, organizational citizenship behavior variable through motivational variable indirectly has no significant positive effect on employee performance variable. Keywords: leadership, competence, organizational citizenship behavior, employee performance, motivation